HAK CIPTA DI UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG - Puspitasari, Sherly; Rohmaniyah, Rohmaniyah (Jurnal Multidisipliner Kapalamada, 2024)
Copyright is an integral part of intellectual property law that provides legal protection for intellectual works produced by individuals or entities. The concept of copyright gives the creator or copyright holder exclusive rights to control the use, distribution and commercial exploitation of his work for a certain period of time. Copyright not only protects specific works, but also provides incentives for creators to continue producing new works by providing economic rewards and recognition for their creative efforts. The copyright system covers various aspects, including types of protected works, limitations on permitted use, registration procedures, and legal sanctions for copyright infringement. Through copyright, society supports innovation, cultural development, and economic growth in the creative industries, while ensuring that creators receive fair credit for their works.